2022
DOI: 10.1039/d2ce01121b
|View full text |Cite
|
Sign up to set email alerts
|

A new 3D 8-connected Cd(ii) MOF as a potent photocatalyst for oxytetracycline antibiotic degradation

Abstract: Incremental use of the antibiotics is now posing pollution problem in aquatic system. Therefore, it is necessary to decompose this class of harmful component existing in wastewater. The metal-organic frameworks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(34 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…In addition to the detection, MOFs have also been widely employed in photocatalysis, like water splitting, CO 2 reduction, organic reactions and so on [ 15 , 16 , 17 , 18 , 19 , 20 ]. The removal of organic pollutants in the waste water is a significant project with the methods like adsorption and in situ degradation [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Among the common pollutants, organic dyes are widely utilized in industrial production, which is in large dosage and strong persistence in the environment resulting in harm to human kidneys and organs [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the detection, MOFs have also been widely employed in photocatalysis, like water splitting, CO 2 reduction, organic reactions and so on [ 15 , 16 , 17 , 18 , 19 , 20 ]. The removal of organic pollutants in the waste water is a significant project with the methods like adsorption and in situ degradation [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Among the common pollutants, organic dyes are widely utilized in industrial production, which is in large dosage and strong persistence in the environment resulting in harm to human kidneys and organs [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 470 and 535 cm −1 were assigned to uniform deformation modes of Zn–O and W–O bonds in ZnO 6 and WO 6 octahedrons, respectively [ 29 ]. In addition, the bands of the O–H stretch and H–O–H bending vibrations were located at 3432 and 1632 cm −1 , which revealed that the synthesized samples contained a notable amount of some structural water and surface-adsorbed water [ 30 , 31 ]. In the fingerprint region, the absorption bands at 535 cm −1 corresponded to the NiO 6 polyhedral in the crystal structure of NiWO 4 , 880 and 830 cm −1 were due to the vibration of the WO 2 entity present in W 2 O 8 group, and 710 and 615 cm −1 were due to the typical two oxygen bridge (W 2 O 8 ) − asymmetric stretching units [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are fascinating porous coordination polymers (CPs), which are made up of organic ligands and metallic cations or metal-containing nodes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Owing to their high intermolecular pores, specific surface area, unsaturated active metal sites, and structural and functional diversities [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], they have adopted a critical interest in various fields, such as energy storage, ion exchange, sensors, drug delivery/release, separation, molecular recognition, catalysis and theranostics [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Compared with some traditional materials such as porous zeolite materials, polymers, and other materials [ 48 , 49 ,…”
Section: Introductionmentioning
confidence: 99%
“…Compared with some traditional materials such as porous zeolite materials, polymers, and other materials [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], MOFs have a specific surface area and volume, a tunable pore size, and a better biocompatibility [ 57 , 58 , 59 ], which make them an ideal candidate for antimicrobial activity and cancer therapy, and so on [ 60 , 61 , 62 , 63 , 64 ]. In addition, MOF porosities and compositions can be tweaked by carefully choosing organic components and metal ions to achieve precise physical and chemical features [ 39 , 65 , 66 , 67 , 68 , 69 ]; and nanoscale MOFs have remarkable loading capacities, which are good for drug loading [ 39 , 40 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%